CREATION OF A CYBEREDUCATION SYSTEM BASED ON DATA SCIENCE: ANALYSIS OF STUDENT ACTIVITY - Qurbonov Behruz Amrulloyevich,; Abdumalikov Nurmuxammad Sherzod o‘g‘li, (Ustozlar uchun, 2025)
Abstract: Cyber threats are one of the main concerns in this growing technology epoch. To tackle this issue, highly skilled and motivated cybersecurity professionals are increasingly in demand to prevent, detect, respond to, or even mitigate the effects of such threats. However, the world faces a workforce shortage of qualified cybersecurity professionals and practitioners. To address this dilemma, several cybersecurity educational programs have been introduced, such as specialized cybersecurity courses in computer science graduate programs. With the increasing demand, different cybersecurity courses are introduced at the high school level, undergraduate computer science and information systems programs, and even at the government level. Due to the peculiar nature of cybersecurity, educational institutions face many issues when designing a curriculum or cybersecurity activities. In this paper, we study existing cybersecurity curriculum approaches and activities. We also present case studies on cybersecurity education around the globe.